Changes of Peripapillary Retinal Nerve Fiber Layer in Childhood Glaucoma: A Systematic Review and Meta-Analysis - Wen, Yuwen; Zhu, Yingting; Zhuo, Yehong (Frontiers in Medicine, 2021)
Objectives: Retinal nerve fiber layer (RNFL) thickness has been detected by numerous studies about alterations and abnormalities in childhood glaucoma, but these studies have yielded inconsistent results about the RNFL thinning region. The investigation of characteristics of RNFL in pediatric patients would contribute to the deep understanding of the neuropathic mechanisms of childhood glaucoma. Thus, the degree of thinning in different quadrants deserves further discussion and exploration. Method: A systematic literature search was conducted using the Cochrane Central Register of Controlled Trials, Medline, Embase, and Pubmed databases to identify clinical studies published from inception to 1 Apr 2021. Results: Ten studies were including in this review, with a total of 311 children with glaucoma and 444 in non-glaucomatous controls. The results revealed that average peripapillary RNFL (pRNFL) thickness was attenuated in pediatric patients with glaucoma (WMD= -20.75; 95% CI, -27.49 to -14.01; P＜0.00001). Additionally, pRNFL thickness in 8 quadrants (superior, inferior, temporal, nasal, sup-temporal, inf-temporal, sup-nasal, and inf-nasal) had different levels of reduction in the pediatric glaucoma group. Conclusion: The present study indicates that eight regions of RNFL thickness show various degrees of thinning in childhood glaucoma. Nevertheless, caution is required in the interpretation of results due to marked heterogeneity. Future studies, especially larger samples and multicenter, need to confirm our results.